Государственная финансовая политика в посткоммунистической Польше - Истер, Джеральд (Вопросы государственного и муниципального управления, 2014)
In the early 1990s, post-communist state actors struggled for the first time with trying to get people to pay taxes. They sought to create new systems of revenue extraction for their quickly changing transition economies. Their immediate concern in devising means of revenue extraction was to break out of the inherited fiscal constraints of the old regime – weak administrative capacity and narrow revenue base. This required finding accommodation with society. Post-communist states cultivated tax compliance in a variety of ways: some states relied more on consent-based strategies, while others adopted more coercive strategies. Poland developed a distinctively non-coercive approach to building capacity and consent, which enhanced the fiscal capacity of the post-communist state. Poland’s strategy of “legalistic consent” as the basis for its new system of revenue extraction proved a smashing success. The fiscal capacity of the post-communist Polish state was suffi ciently strengthened to overcome the crippling initial domestic fiscal crisis and to withstand the fiscal shocks of two international fi nancial crises in 1998 and 2008.